"Misalignments between users and designers as source of inspiration: A novel hybrid method for physical new product development". (March 2022) - Granato, Giulia; Fischer, Arnout R.H.; van Trijp, Hans C.M.
Abstract: This paper replies to the call for more agile-stage-gate hybrid methods in the context of physical innovations. By showing how some of the characteristics of conventional linear stage-gate methods and of the agile approaches can be integrated, we propose and test a new form of hybrid method for the physical new product development process (NPD). Distinguishing itself from the conventional NPD methods and practices, biased towards alignments between companies and consumers as the key to market success, our method focuses on the innovation potential intrinsic to misalignments. Through a qualitative research applied in an existing European consortium of innovators, the present work guides companies in the systematic identification and exploration of misalignments between their designers and users. By identifying misalignments at specific level of the NPD process, our method provides companies with a deep analytical insight into how, where and why (mis)alignments between their designers' decisions and users' demands might occur. Our method revealed to be a strategic learning and reflection tool to support companies in the proactive management of the identified misalignments, as informative, beneficial and inspirational aspects of the NPD process. Highlights: The combination of agile and stage-gate methods can deliver analytical and strategic insights for the company. The means end chain approach is useful to compare companies' and consumers' perspective on the same innovation. Hybrid stage-gate and agile methods can be used to identify and exploit misalignments between designers and users.